Implications of Creating Solution Concepts Based on the Use of References. (May 2022) - Schlegel, M.; Pfaff, F.; Rapp, S.; Albers, A.
Abstract: The use of already validated systems as references for the development of solution concepts offers the potential to increase process efficiency. It is important to understand how the use of references impacts the development of solution concepts. Therefore, the representation of solution concepts in an engineering project of two student cohorts are analyzed and compared. The first cohort is provided with few and the second cohort with extensive references. The results of the study show that the increased use of references leads to a higher share of embodiment and specific challenges.